2007
DOI: 10.1254/jphs.fp0070039
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-1 Induces Contraction via a Syk-Mediated p38 Mitogen-Activated Protein Kinase Pathway in Rat Aortic Smooth Muscle

Abstract: Abstract. Although spleen tyrosine kinase (Syk) has crucial roles in various cells, its function on vascular smooth muscle contraction has not been determined. In the present study, we performed experiments to determine if Syk contributes to the endothelin-1 (ET-1)-mediated contraction in rat aortic smooth muscle. ET-1-induced contraction of aortic strips was inhibited by piceatannol, PD98059, and SB203580, inhibitors of Syk, extracellular signal-regulated kinase 1 / 2 (ERK1/ 2), and p38 mitogen-activated prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 35 publications
2
26
0
Order By: Relevance
“…In many smooth muscles, p38 MAPK activation is linked to contraction (10,29,34,36,56), and in vascular tissues and gastrointestinal smooth muscle cells, Hsp27 phosphorylation is important for sustained contraction (32,40). Although in rat aorta smooth muscle cells, the inhibition of p38 MAPK and Hsp27 showed a significant reduction in contraction to ANG II but not NE (34).…”
Section: Discussionmentioning
confidence: 99%
“…In many smooth muscles, p38 MAPK activation is linked to contraction (10,29,34,36,56), and in vascular tissues and gastrointestinal smooth muscle cells, Hsp27 phosphorylation is important for sustained contraction (32,40). Although in rat aorta smooth muscle cells, the inhibition of p38 MAPK and Hsp27 showed a significant reduction in contraction to ANG II but not NE (34).…”
Section: Discussionmentioning
confidence: 99%
“…Some drugs are also known to contract smooth muscle 2,3) . Many previous studies, including our own, have reported on signal transduction mechanisms and smooth muscle contractions [4][5][6][7][8][9][10][11][12][13][14] . In spite of the importance of the smooth muscle in the fields of cardiovascular physiotherapy, obstetrics, and clinical methods, there is still a need for more research [15][16][17] .…”
Section: Introductionmentioning
confidence: 89%
“…Syk is also found in bronchial smooth muscle and has attracted attention because of its role in hypertension and the emigration of smooth muscle related to arteriosclerosis (Fig. 11-B) 11,91,92) . The N-terminal of Syk protein has two Src-homology 2 (SH2) domains.…”
Section: ) Syk Protein Tyrosine Kinase (Syk) Involvement In Smooth Mmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, elevated ET-1 levels lead to NADPH oxidase activation and superoxide formation via ET A receptors, resulting in excessive ROS production and endothelial dysfunction [14]. Other studies have demonstrated that the kinases (p38 MAPK, ERK1/2) and NF-κB signaling pathways take part in the regulation of ET-1 in response to a variety of stimuli [15].…”
Section: Introductionmentioning
confidence: 99%